JPEG Privacy and Security framework for social networking and GLAM services - Frederik Temmermans; Touradj Ebrahimi; Siegfried Foessel; Jaime Delgado; Takaaki Ishikawa; Ambarish Natu; Peter Schelkens (EURASIP Journal on Image and Video Processing, 2017)
Abstract Current image coding standards provide limited support for privacy and security features. An exception is the JPSEC standard, which defines security extensions in JPEG 2000 specifications (part 8). Notwithstanding this shortcoming, the JPEG committee is currently defining a new JPEG Systems standard, which envisages privacy and security support across JPEG family of standards. In this manuscript, the main philosophy of this emerging specification is outlined along with typical use cases, main requirements as well as examples of potential technological solutions. The upcoming specification guarantees backward and forward compatibility with earlier standards and legacy implementations. Finally, we illustrate the introduced framework by two applications targeting secure photo sharing on social networks and IPR management in the GLAM sector.